Judicialization of health: knowledge of nursing, medicine and law students (Research, Society and Development, 2021)
This study aimed to analyze the knowledge of Nursing, Medicine and Law students about the judicialization of health. This is a quantitative, exploratory and descriptive study, carried out with 117 students from the nursing, medicine and law courses, through the application of a questionnaire prepared by the authors of the work. Data collection took place from March to May 2019. The analysis took place using the statistical software Statistical Package for Social Sciences version 22.0. Based on the results, in relation to academic training, students point out that there is a need for greater emphasis on the development of ethical, critical and reflective thinking for the judicialization of health. Thus, it can be concluded that there is a need for discussion and expansion of spaces for academic and professional training in health and law courses regarding the judicialization of health.